Textual Meaning of the Lecturers’ Utterances and Gestures Used in Teaching Reading and Writing: A Systemic Functional Multimodal Discourse Analysis (SFMDA) - Sri Mulatsih; Issy Yuliasri (Universitas Negeri Semarang, 2021)
Lecturers’ utterances, and gestures are two modes that are important in the teaching and learning processes. These two modes contribute meanings that support those processes. Those meanings can be ideational, interpersonal, or textual ones. This study is aimed at describing the textual meaning of the lecturers’ utterances and gestures used in teaching Reading and Writing. A systemic functional multimodal discourse analysis (SFMDA) proposed by Lim (2011) was used as the framework of the study. The data in this study are in the form of utterances (spoken languages) produced by two lecturers and gestures used during the teaching of Reading and Writing. The qualitative data which are in the form of the lecturers’ utterances and gestures were analyzed using qualitative data analysis offered by Creswell (2009). The results showed that the textual meaning of the lecturers’ utterances are realized in many types of theme and rheme. The themes mostly used in the utterances of both lecturers in Reading and Writing are topical (unmarked) because they use the topics being discussed in the classrooms as the subject of the clause. Interpersonal theme is also used in “wh” interrogative to ask the students about the topics being discussed. The textual meaning of the lecturers’ gestures are realized in two ways, they are pointing directionality and pointing specificity. Pointing specificity is used more than pointing directionality because the lecturers mostly performed specificity pointing to the students using hands, or certain fingers. Directionality pointing is also performed to the white board or screen.